The Effect Of Gadget Use Intensity On Emotion Regulation In Elementary School-Age Children - Rian Maulana Yusup; Eti Wati (Sean Institute, 2024)
Not only does the use of gadgets in school-aged children have positive impacts, it also has negative impacts, one of which results in addiction, making children always feel anxious, irritable and unable to control their emotions when asked to stop playing with gadgets. The increasing prevalence of gadget use is continuous with the frequency and duration spent in using gadgets due to the fear of being left behind. In addition, excessive gadget use can cause emotional changes. This study aims to determine the relationship between the intensity of gadget use and emotional regulation in children aged 6-12 years at Elementary Schools in Majalengka Sub-district. This type of research uses quantitative research with a cross sectional approach. The population in this study were children aged 6-12 years, totaling 230 children and the sample was 70 children with purposive sampling technique. This research instrument used a questionnaire and analyzed the data using the chi square test. More than half (57.1%) of children aged 6-12 years have high gadget intensity and less than half (45.7%) of children aged 6-12 years have poor emotional regulation. There is a relationship between the intensity of gadget use and emotional regulation in children aged 6-12 years with p value = 0.000. Conclusion: emotional regulation is influenced by gadget intensity, so it is necessary to make a clear and consistent gadget use schedule, provide alternative interesting and educational activities and educate children about healthy gadget use.